IMPLEMENTASI PEMOTONGAN PAJAK PPH PASAL 4 AYAT 1 ATAS JASA HONORARIUM DAN IMBALAN PNS DILUAR GAJI PADA KANTOR BAPENDA KABUPATEN BULUKUMBA - nasrullah nasrullah; Pratiwi Hamzah; Andi Arifwangsa Adiningrat; Yuyun Wahyuni Sukma (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to determine the implementation of withholding income tax article 4 paragraph 1 on honorarium and compensation for civil servants outside of salary at the BAPENDA BULUKUMBA. district office. This type of research is a qualitive descriptive study. Where research is carried out in the field and the survey is directly in place to be studied. Research Result Based on data obtained from the Bapenda of Bulukumba Regency and the data processing carried out by researchers according to the PPh 1984 Law that the income subject to taxatipn has the following elements, that what includes income is any addictional ability to control goods and service obtained by the taxpayer, the ratte of withholding income tax articel 4 paragraph 1.